High-resolution parameter space of an experimental chaotic circuit - Viana E.R. (2010)
A high-resolution codimension-two parameter space showing the abundance of complex periodic structures of an experimental chaotic circuit is reported. Such resolution was propitiated by the use of a 0.5 mV step dc voltage source as one of the control parameters. Those complex periodic structures organize themselves in a period-adding bifurcation cascade that accumulates in a chaotic region. Numerical investigations on the dynamical model were also carried out to corroborate several new features observed in the experimental high-resolution parameter space. © 2010 American Institute of Physics.